Analysis and comparison of the South African and Eurocode live load models for railway bridges - Paulse, Sheryl Dawn (Department of Civil Engineering, 2019)
This dissertation is an analytical study that compares the South African Transport Services (SATS) and Eurocode (EC) live load models for railway bridges. The study is specifically concerned with the critical load effects of shear and bending moment. The load models are simulated as moving loads over the full length of simply supported and continuous railway systems with speeds not exceeding 180km/h. The study is limited to short to medium spans ranging from 5m – 40m analysed in increments of 5m. The position of the maximum load effects for simply supported systems was determined using the frame analysis module in Prokon. Maximum load effects were determined using the influence line method. Maximum load effects for the continuous systems were determined using the moving load option in STRAP. It was found that SATS live load models imposed on single span railway bridges, produce conservative load effects for short span bridges but become over conservative with an increase in span, when compared with characteristic values of the EC load model 71 (LM71). For heavy loads (α = 1,10) in LM71, there is a good comparison with that of the EC for static and design moment (for a track with standard maintenance) with values of 5% lower at 10m but become moderately conservative (2% - 5%) with an increase in span. In the case of design bending moment (for a carefully maintained track) the SATS code is moderately conservative (6% - 8%) over the full range of spans for a carefully maintained track. For heavy loads (α = 1,10) in LM71, there is a good comparison with that of the Eurocode for static and design shear (for a carefully maintained track) with values of 4% lower at 10m but becoming moderately conservative (1% - 5%) with an increase in span. In the case of design shear (for a track with standard maintenance) the SATS code compares well with that of the EC, with values of 5% lower at 10m but becoming moderately conservative (4% - 13%) with an increase in span. Live traffic loads imposed on equal span (limited to 2) continuous railway bridges, produce conservative static and design shear load effects (for a carefully maintained track) in the mid-range of spans but become moderately conservative with increase in span for heavy loads (α = 1,10) for load model SW/0. There is a good comparison with that of the EC for design shear force (for a carefully maintained track) with moderately conservative (1% - 9%) for short span and long span systems for heavy loads (α = 1,10) for load model SW/0. A similar comparison occurs for heavy loads (α = 1,21) for SW/0 for static and design shear for a carefully maintained track. Live traffic loads imposed on equal span (limited to 2) continuous railway bridges produce over conservative static bending moment load effects for short span and long span bridges (2 x 30m – 2 x 40m) for characteristic values and heavy loads (α = 1,10 and α = 1,21) for load model SW/0. Generally, there is not a good comparison with that of the EC for static and design bending moment, for two span continuous railway bridges. Live traffic loads imposed on equal span (limited to 3) continuous railway bridges produce moderately conservative static shear force effects for heavy loads (α = 1,10 and α = 1,21) for load model SW/0. The only significant value is at the 3 x 5m span (21% higher) and the 3 x 15 – 3 x 20m range of spans (9% - 10% lower) for heavy loads (α = 1,10) and (α = 1,21) respectively. A similar comparison is observed for design shear effects for both types of track for heavy loads (α = 1,10) and (α = 1,21) for a carefully maintained track. Generally, there is not a good comparison with that of the Eurocode for static and design bending moment, for three span continuous railway bridges.